Low-Flow Pressure Gradient Pumping for Active Absorption of CO2 on a Molecular Sieve. Issue 2 (14th December 2016) - Cheng, Peng; Wu, Shugang; Fu, Yunchong; Xiong, Xiaohu; Niu, Zhenchuan; Fan, Yukun
Abstract: The authors have developed an active absorption system combining a molecular sieve with a pressure gradient as a way to overcome the shortcomings of the phosphoric acid solution displacement method. Taking advantage of the pressure gradient produced between the inside and outside of a bottle, as water moves through it, CO2 in the atmosphere can actively be absorbed onto a molecular sieve in its pathway. A comparative study showed that the technique was in agreement with the phosphoric acid displacement method, within error. We applied the new method to collect not only atmospheric CO2 samples, but also CO2 samples from soil respiration to verify its utility. Simple yet practical, our method is well suited to extended collection times in a variety of environments, and capable of providing relatively large amounts of carbon for high-precision accelerator mass spectrometry (AMS) 14 C analyses of atmospheric samples.